NEUROPROTECTIVE ROLE OF VITAMIN D3 ON GANGLION CELL-INNER PLEXIFORM LAYER THICKNESS IN NMDA-INDUCED RETINAL EXCITOTOXICITY MODEL OF GLAUCOMA: (Experimental Study on Wistar Rats Glaucoma Model with N-Methyl-D-Aspartate induction) - Maharani; Margareth, Ezra; Nugroho, Trilaksana; Dharma, Andhika Guna; Rahmi, Fifin L; Istiadi, Hermawan (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesRetinal ganglion cell (RGC) damage can affect the thinning of the GCC layers, which is the nervefiber layer, the ganglion cell layer and the inner plexiform layer. The loss of RGC and inner plexiformlayer (IPL) is strongly correlated with the loss of visual field defect. RGC and inner plexiform layerare potential targets to evaluate the progression of glaucoma. Glaucoma treatment not only focus onreducing IOP. Decreasing IOP according to the target pressure often can’t stop the process of RGCdamage and make it permanently and irreversible. Vitamin D3 is known as neuroprotector which hasthe ability to protect RGC and prevent layer thinning of GC-IPL in retina. The aim of this study is todetermine the effect of oral Vitamin D3 on the GC- IPL layer thickness in retinal of Wistar rats withNMDA-induced glaucoma model. MethodsGlaucoma Wistar rats were divided into 2 groups. The treatment group was given oral Vitamin D3 ata dose of 500 IU/kgBW/day for 10 weeks. GC-IPL layer thickness in retinal was examined byHematoxylin Eosin staining. Data were collected and processed then used with Independent T Test.(significant p<0.05) ResultsThe mean GC-IPL layer Thickness in the treatment group was 77,59 ± 15,15 ?m and 35,32 ± 4,04?m in the control group. There was a significant different between two group ( p = <0,001 ) ConclusionVitamin D3 has a neuroprotective effect on ganglion cell-inner plexiform layer Wistar rats in NMDAinducedexcitotoxicity model of glaucoma